Efisiensi Teknis Bank Pembangunan Daerah di Indonesia Periode Tahun 2009 sampai dengan 2011 - Atman Poerwokoesoemo (Indonesia Banking School, 2014)
The purpose of this research is to measure the technical efficiency of the 26 Rural Development Bank in Indonesia for 2009 to 2011 based on Farrelâ€™s method and implementing the assumption of the efficient production continuous function to take the form of Cobb-Douglas production function. Technical efficiency measured involving two input variable; Capital and Total Employee and one output variable Loan. The result of this research shows that the Cobb-Douglass parameter ï¡ = 0.683 dan ï¢ = 0.317. Among the 26 Rural Development Bank shows that 2 banks consistently maintain its technical efficiency level in the range of 80 to 100%, 2 banks maintains its technical efficiency level in the range between 60 to 80%, 13 banks lays below 60% and the remaining 9 banks are moved up and down along the three years period.